2020
DOI: 10.3390/plants9081029
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Embryogenesis and Plant Regeneration from Sugi (Japanese Cedar, Cryptomeria japonica D. Don, Cupressaceae) Seed Families by Marker Assisted Selection for the Male Sterility Allele ms1

Abstract: One of the possible countermeasures for pollinosis caused by sugi (Cryptomeria japonica), a serious public health problem in Japan, is the use of male sterile plants (MSPs; pollen-free plants). However, the production efficiencies of MSPs raised by conventional methods are extremely poor, time consuming, and resulting in a high seedling cost. Here, we report the development of a novel technique for efficient production of MSPs, which combines marker-assisted selection (MAS) and somatic embryogenesis (SE). SE f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…In this context, the development of technology to produce excellent MSPs in a short period of time is one of the priority goals. At present, efficient protocols to propagate male-sterile somatic plants of sugi combine a selection of ECs with marker-assisted selection and propagation via SE has been established [ 19 ]. On the other hand, as one of the methods for labor-saving production of genetically diverse seedlings, it is conceivable to use seeds derived from polycross pollination, artificial mating using mixed pollen from multiple parents.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the development of technology to produce excellent MSPs in a short period of time is one of the priority goals. At present, efficient protocols to propagate male-sterile somatic plants of sugi combine a selection of ECs with marker-assisted selection and propagation via SE has been established [ 19 ]. On the other hand, as one of the methods for labor-saving production of genetically diverse seedlings, it is conceivable to use seeds derived from polycross pollination, artificial mating using mixed pollen from multiple parents.…”
Section: Introductionmentioning
confidence: 99%
“…SE is a biotechnological tool which consists in the dedifferentiation of somatic cells and their subsequent cell re-differentiation in somatic embryos (ses), through genetic reprogramming [10]. Based on the morphogenetic response, SE is widely used to obtain large amounts of cloned material from elite material in response to an external stress stimulus [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the application of biotechnology to produce superior male-sterile trees in a short period of time is one of our main priorities. Now, efficient protocols to propagate male-sterile somatic plants of sugi involve combining the selection of embryogenic cells (ECs) with marker-assisted selection, and propagation through SE has been established [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since SE was first reported for spruce species, numerous studies on conifer trees have been reported [ 10 , 11 , 12 ]. For sugi, after the first report on plant regeneration via SE [ 13 ], more results including studies on SE initiation [ 14 , 15 , 16 , 17 , 18 ], somatic embryo maturation [ 19 , 20 , 21 , 22 ], plant conversion [ 9 , 23 ], cryopreservation [ 24 , 25 ], and plant transformation [ 26 , 27 ] were published, showing progress in optimizing SE protocols. However, detailed reports on the factors influencing somatic embryo maturation in several ECLs from different seed families of sugi have not yet been published.…”
Section: Introductionmentioning
confidence: 99%